Submarine cables: a vector for export sophistication in sub-Saharan Africa? - (:unkn) unknown (My University, 2023)
Sub-Saharan Africa (SSA) plays a very marginal role in world trade. Possible reasons for this relative marginalization include high transaction costs, a deficient infrastructure network and structural handicaps linked to unfavorable geographical factors. Despite rapid growth rates over the past two decades, sub-Saharan African countries have not followed an industrialization path that would allow them to catch up with post-independence income levels (Rodrik, 2016). However, with the recent massive deployment of submarine cable connectivity infrastructure in SSA and the resulting increase in internet penetration (Cariolle, 2021), information and communication technologies are increasingly seen as a revolutionary solution for the region.
Keywords: African Research